The political economy of Chinese internet companies: Financialization, concentration, and capitalization. (January 2018) - Jia, Lianrui; Winseck, Dwayne
The rapid growth of the internet in China has been propelled by the Chinese government's push to develop the country's information infrastructure and its tight control over the internet. The most recent stage of internet development in China, however, has been driven by a three-way dynamic between the State, internet companies, and international finance capital. This relationship has yielded three internet giants—Baidu, Alibaba, and Tencent—that stand at the apex of the internet economy in China. They also rival their US counterparts like Google, Facebook, and Amazon, on several key measures. We examine annual reports and other financial documents to better understand these three companies' character as 'capitalist enterprises' and the tight nexus that links them to international investment banks, venture capital funds, and other foreign investors. While these processes are now fundamentally shaping 'the Chinese internet', they have not yet been adequately explored in the scholarly literature, we argue.